Phase I trial of a standalone internet social anxiety treatment for adolescents who stutter: iBroadway. Issue 6 (30th July 2019) - Gunn, Anthony; Menzies, Ross G.; Onslow, Mark; O'Brian, Sue; Packman, Ann; Lowe, Robyn; Helgadóttir, Fjóla Dögg; Jones, Mark
Abstract: Background: iGlebe is a fully automated internet treatment program for adults who stutter that has been shown, in some cases, to reduce anxiety and effectively manage social anxiety disorder for many participants. No such automated internet treatment program exists for adolescents who stutter. Aims: The present paper reports a Phase I trial of an adolescent version of the adult program: iBroadway. Methods & Procedures: Participants were 29 adolescents in the age range 12–17 years who were seeking cognitive–behaviour therapy (CBT) for anxiety associated with stuttering. The design was a non‐randomized Phase I trial with outcome assessments at pre‐treatment and immediately post‐treatment after 5 months of access to the program. No contact by a clinical psychologist occurred during participant use of the program. Outcomes were a range of psychological, quality‐of‐life and stuttering severity measures. Outcomes & Results: The compliance rate for the seven iBroadway modules over 5 months was extremely favourable for internet CBT, at 52.4%. There was evidence of treatment effects for (1) the number of DSM‐IV mental health diagnoses with the Diagnostic Interview Schedule for Children; (2) the Unhelpful Thoughts and Beliefs About Stuttering scale; (3) the Subjective Units of Distress Scale; and (4) parent‐reported speech satisfaction. Conclusions & Implications: Further development of iBroadway, the adolescent version of iGlebe, with Phase II trialling is warranted.